FIRST RECORD OF AEDES ALBIFASCIATUS IN MAGALLANES REGION, CHILE - Carvajal, Mariom A.; Faundez, Eduardo (My University, 2018)
Aedes albifasciatus is known for transmitting western equine encephalomyelitis (WEE), a virus that can affect humans and animals. In this work, we record for the first time Ae. albifasciatus from the Magallanes Region in Chile, as the only culicid species known from this southernmost region. Although WEE poses a serious problem to cattle production in neighboring Argentina, no WEE has been recorded in Chile. The need for surveillance programs of WEE in Magallanes is also discussed here.
Keywords: culicidae; first record; magallanes; patagonia; western equine encephalomyelitis